Cyclosporine A: Novel concepts in its role in drug-induced gingival overgrowth - Deepa Ponnaiyan; Visakan Jegadeesan (Wolters Kluwer Medknow Publications, 2015)
Cyclosporine is a selective immunosuppressant that has a variety of applications in medical practice. Like phenytoin and the calcium channel blockers, the drug is associated with gingival overgrowth. This review considers the pharmacokinetics, pharmacodynamics, and unwanted effects of cyclosporine, in particular the action of the drug on the gingival tissues. In addition, elucidates the current concepts in mechanisms of cyclosporine-induced gingival overgrowth. Clinical and cell culture studies suggest that the mechanism of gingival overgrowth is a result of the interaction between the drug and its metabolites with susceptible gingival fibroblasts. Plaque-induced gingival inflammation appears to enhance this interaction. However, understanding of the pathogenesis of gingival overgrowth is incomplete at best. Hence, it would be pertinent to identify and explore possible risk factors relating to both prevalence and severity of drug-induced gingival overgrowth. Newer molecular approaches are needed to clearly establish the pathogenesis of gingival overgrowth and to provide novel information for the design of future preventive and therapeutic modalities.